2003
DOI: 10.1385/bter:94:3:213
|View full text |Cite
|
Sign up to set email alerts
|

Selenoenzyme Activities in Seleniumand Iodine-Deficient Sheep

Abstract: This study was conducted to evaluate the effects of single and combined deficiencies of selenium and iodine on selenoenzyme activities in sheep. Twenty-four male lambs were assigned to one of four semisynthetic diets: combined deficient A (Se-I), Se-deficient B (Se-I+), I-deficient C (Se+I-), and basal diet D (Se+I+). Thyroid hormones (T3, T4), thyroid stimulating hormone (TSH), and inorganic iodine (PII) were determined in plasma. Selenium and glutathione peroxidase activity (GSH-Px) were determined in erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…Our study also showed that the mRNA levels of other selenoproteins (Gpx1, Gpx4, Sep15, Sepp1, Selk1, Selm, and Sbp2) were not modulated by I Ϫ treatment. Although it has been demonstrated that Se supply is directly associated with the control of selenoprotein expression (29,56,57), our results showed that Se supplementation (from 50 -500 nM) of cells treated with I Ϫ excess did not exert effects on selenoprotein modulation other than those reported here (data not shown).…”
contrasting
confidence: 86%
“…Our study also showed that the mRNA levels of other selenoproteins (Gpx1, Gpx4, Sep15, Sepp1, Selk1, Selm, and Sbp2) were not modulated by I Ϫ treatment. Although it has been demonstrated that Se supply is directly associated with the control of selenoprotein expression (29,56,57), our results showed that Se supplementation (from 50 -500 nM) of cells treated with I Ϫ excess did not exert effects on selenoprotein modulation other than those reported here (data not shown).…”
contrasting
confidence: 86%
“…Although the effects of Se deficiency on thyroid hormone metabolism have been studied extensively in a number of animals [5,6] including chicken [7], very little is known about the influence of excess Se on thyroid hormone metabolism and selenoenzyme activities. In humans, Se supplementation led to variable results, depending on the Se status of the examined population group, extending from non to substantial changes in thyroid function [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Se was identified as a component of type I iodothyronine-5-deiodinase, the enzyme that converts T4 to T3 [1]. In addition, the effects of Se and/or iodine deficiency on the selenoenzymes activity in sheep were recently described [2]. An important interrelationship exists between Se, vit E, and the sulfur-containing amino acids in preventing some of the nutritional diseases caused by their deficiency [3].…”
Section: Introductionmentioning
confidence: 99%